Trans-subclavian Valve-in-Valve TAVR in a Patient with Previous Bio-Bentall and Open Coarctation Repair - Christopher Gasparis; Michele Dell'Aquila; Danielle I. Aronowitz; Sarah Kalimi; Branden Tejada; Omar Jarral; Frank Manetta; Joshua Newman; John Goncalves; Robert Kalimi (International Journal of Angiology, 2026)
Abstract Valve-in-valve transcatheter aortic valve replacement (TAVR) may offer improved in-hospital outcomes compared with reoperative surgical aortic valve replacement (SAVR) and is especially helpful in patients with elevated surgical risk. In this report, we describe a 53-year-old man with history of coarctation, bicuspid aortic valve, and ascending aortic aneurysm who underwent graft repair of his coarctation as well as modified Bentall root replacement, and who presented with acutely worsening chest pain and dyspnea on exertion. Left heart catheterization revealed severe bioprosthetic aortic valve stenosis without significant coronary artery disease. Valve-in-valve TAVR was performed via the left subclavian artery. The patient had complete symptom resolution on follow-up.